Dampak Pandemi COVID-19 Terhadap Implementasi Target Energi Terbarukan dalam Kerangka ASEAN Plan of Action for Energy Cooperation 2016-2025 - Alynka Putri Adhitama; Hartanto Hartanto (Universitas Serang Raya, 2023)
The energy transition from using energy fossils to cleaner renewable energy is one of the ways to achieve energy security. ASEAN in an attempt to promote the energy transition and sustainable energy growth set an aspirational target to increase the component of renewable energy to 23% by 2025 in the ASEAN energy mix which is included in one of the key programs in the ASEAN Plan of Action for Energy Cooperation (APAEC) 2016-2025. However, because of the Covid-19 pandemic, there will be challenges in the implementation of this renewable energy target. This paper will explore the impact of the Covid-19 pandemic on the implementation of renewable energy target in the APAEC 2016-2025 framework. The use of literature reviews as the research method to gather information and data about the topics about covid-19 pandemic impact on the renewable energy sector in ASEAN and then give a conclusion about these events. Furthermore, this paper will tell about ASEAN's policy measures to achieve the renewable energy target of APAEC 2016-2025.